The Emerging Role of Pharmacotherapy in Obstructive Sleep Apnea - Nikhil Jaganathan; Younghoon Kwon; William J. Healy; Varsha Taskar (Journal of Otorhinolaryngology, Hearing and Balance Medicine)
Obstructive sleep apnea (OSA) is a prevalent pathology with current modalities of treatment including continuous positive airway pressure (CPAP), surgery, weight loss, hypoglossal nerve stimulation, and pharmacotherapy. While CPAP is the current standard treatment for OSA, lack of tolerance and side effects necessitate alternative modalities of treatment. Various pharmacologic agents exist with mechanisms that may target OSA. Early trials have demonstrated efficacy of noradrenergic-antimuscarinic combinations to stimulate the airway, promote pharyngeal muscle tone, and prevent airway collapse. These agents, which we discuss in detail, have demonstrated significant reductions in apnea-hypopnea index (AHI) and lowest oxygen saturations based on preliminary studies. Glucagon-like peptide 1 receptor agonists (GLP-1RA), which stimulate endogenous insulin, reducing glucagon release, and decreasing gastric emptying, have shown positive results for OSA patients through weight loss with reductions in AHI. In this narrative review article, we highlight the mechanisms, current data, and future potential for multiple drug classes, including respiratory stimulants and GLP-1RAs.